A MODEL OF THE SELF-STRESS STATE OF THE SEDIMENTARY ROCK AND ITS APPLICATION TO ESTIMATION OF RESIDUAL EFFECTS - A. I. Moroz (Геодинамика и тектонофизика, 2015)
Based on analysis of modern concepts describing changes in the stress-and-strain state of rocks, it is revealed that the elastic energy is not fully released and residual/own stresses occur in core samples taken out of the rock massif.The paper describes a model aimed at explanation of causes for residual stresses of the type. The model is composed of two elastic elements that are subject to different states of stresses; it shows major previous stages of formation of the initial state of gravity stresses of the detrital sedimentary rock which were followed by cementation and changes of the state of stresses during unloading. Being an element of the history, the sequence of formation of the rock under the ‘loading – cementing’ pattern leads to formation of two systems of stresses in the rock elements (according to K. Terzaghi), i.e. effective stresses in the rock matrix (or groundmass) that is subject to main loading, and neutral stresses in the connate fluid that is not involved in the process. Upon hardening of the solution, the effective stresses become bound by the cementing material.Changes of the stress-and-strain state of the model in case of induced or natural unloading are analyzed on the basis of stress–strain curves that are reconstructed for the rock elements prior to unloading and compared in the same systems of coordinates, and the process of unloading is reviewed with account of the condition of their joint deformation. By applying the method of superposition of the two fields of stresses during unloading, it is possible to reveal the cause-and consequence relationship between the initial state of stresses and the occurrence of own stresses and, subsequently, to trace the self-stress state. The proposed definition ensures a ‘transparent’ representation of changes of stresses between the model’s elements during unloading, changes of the potential energy and distribution of its components after unloading, which provides an explanation of the incomplete release of the potential energy.